KNOWLEDGE, ANXIETY AND MANAGEMENT OF STUNTING THROUGH ROLES OF MOTHER: A SYSTEMATIC REVIEW - Essy Sonontiko Sayekti; Anisah Ardiana (UPT Penerbitan Universitas Jember, 2023)
Backgrouds: Stunting is a condition of a child under 5 years old who is low height-for-age. A mother as the closest person to a child is the support system for the child growth with stunting. A mother needs to have an adequate knowledge to be able to take care of the child with stunting, so that the child can optimally develop. The condition of a child with stunting might cause anxiety for a mother. This study is aimed to analyze the management of stunting through roles of mother to enhance mother’s knowledge and to decrease mother’s anxiety in dealing with a child with stunting. Methods: The method of this study is literature review using three electronic database including PubMed, Google Scholar and ProQuest. The focus of the journals to review is international journals which are published in the last 5 years available in full text. Result: A total of 54.600 articles were identified. 13 articles were analyzed show that the knowledge of the mothers is influenced by the information about stunting through media and health care providers. The positive attitude of mothers and their psychological condition need to be kept in attention to support the treatment of their children with stunting optimally. Conclusion: A mother with a stunting child requires good knowledge about how to take care her child properly. Having adequate knowledge, a mother will be able to manage her anxiety and hopefully able to provide optimal treatment for her child.